TH2/TH1 Shift Under Ibrutinib Treatment in Chronic Lymphocytic Leukemia - Puzzolo, Maria Cristina; Del Giudice, Ilaria; Peragine, Nadia; Mariglia, Paola; De Propris, Maria Stefania; Cappelli, Luca Vincenzo; Trentin, Livio; Reda, Gianluigi; Cuneo, Antonio; Molica, Stefano; Piciocchi, Alfonso; Arena, Valentina; et al. (Frontiers in Oncology, 2021)
Ibrutinib may revert the T-helper (Th)2 polarization observed in chronic lymphocytic leukemia (CLL) by targeting the IL-2-inducible kinase, that shows a significant homology with the Bruton tyrosine kinase. In the front-line GIMEMA LLC1114 trial (ibrutinib+rituximab for 6 months, followed by ibrutinib maintenance), we investigated the modulation of T-cell cytokine production in 208 peripheral blood paired samples from 71 CLL patients: 71 samples prior to treatment (Day 0, D0) and at day +14 (D14; n=50), at month +8 (M8; 30), +12 (M12; 25), +18 (M18; 22) and +24 (M24; 10) of treatment. We documented a progressive decrease of CD3+CD4+IL-4+ T cells (Th2), that was significant at M8 and at M12 (p=0.019, p=0.002), a relative increase in the CD3+CD4+IFNγ+ T cells (Th1) and a decrease of CD3+CD4+IL-17+ (Th17) cells that was maintained up to M18 (M8 vs D0 p=0.003, M12 vs D0 p=0.003, M18 vs D0 p=0.004) of ibrutinib treatment. The Th2/Th1 ratio significantly decreased already after 14 days of treatment and was maintained thereafter (D14 vs D0 p=0.037, M8 vs D0 p=0.001, M12 vs D0 p=0.005, M18 vs D0 p=0.002). The Th2/Th1 modulation over time was significant only among patients with unmutated IGHV. The Th2/Th1 ratio below a cut-off of 0.088 at M8 was associated with the achievement of a complete response (CR) (p=0.016). Ibrutinib may shape the CLL T-cell profile, limiting Th2 activation and inducing a shift in the Th2/Th1 ratio. The association between the Th2/Th1 ratio decrease and the CR achievement suggests the in vivo generation of a potential host anti-tumor immune activation induced by ibrutinib.